The Performance of European Mutual Funds Under Bull and Bear Market Conditions - Galea, Daniel (2020)
This paper examines the performance of 228 European active equity mutual funds from the five most dominant mutual fund countries relative to their peer indices, analysed through the use of several risk-adjusted metrics and four different factor models. The evaluation is carried out over the period between 2000 and 2019 and further sub-divided into phases of major bull and bear market cycles. Our results show that on a risk-adjusted basis, European mutual funds are only able to provide investors with superior returns during extended up-market trends, failing to exhibit signs of outperformance in any other period considered. We find statistically significant abnormal return generation for the majority of Europe over the whole 19-year horizon and absolute significant outperformance in extended bullish episodes, specifically in the case of small cap funds. In line with the general consensus inherent in previous studies, active portfolios do not produce positive or significant alphas during bear market movements. Overall, save for the analysis carried out throughout the Great Recession, UK-domiciled mutual funds document the most consistent indication of promising performance. Conversely, Spanish funds offer unsatisfactory returns during four of the five phases considered, adding little value to the argument put forth by proponents of active fund management and market inefficiency.